Litteratur samt nyudkommen litteratur - Brynolf Honkasalo; Ivar Strahl; Knud Waaben; Jon Johnsen; Louis Le Maire; Allan Philip (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews and new litterature